MERANGKAI KONSEP HARGA JUAL BERBASIS NILAI KEADILAN DALAM ISLAM - Alimuddin Alimuddin (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
This paper aims to explore and discuss the justice value in Islam in order to formulate price concept based on justice value in Islam. The second aim is to find out the benefits of the price concept for mashlahah of mankind. The analytical method employed in this paper is a critical-intuitive thinking based on Islamic epistemological framework, that is the bayani method, burhani method and irfani method. The bayani mothod is a textual presentation from text, event or phenomenon while the burhani mothod is based on logic to understand events and phenomena or to interpret the text contextually. While irfani mothod places greater reliance on intuition to achieve scientific knowledge. The three methods are applied integratedly in this paper. The study was conducted on the owners and management YDT in Bandung. The results showed, the price concept based on justice value according to bayani method is cost-plus profane basic needs and according to burhani  method is cost-plus basic needs as well as according to irfani method is cost-plus basic needs and environment. In general, the price concept based on justice value in Islam is cost-plus pricing, which is a concept that considers pricing benefit for mashlahah of mankind in determining the amount of margin through a balance between the needs of traders with the basic needs of the buyer's purchasing power and the need to preserve and maintain harmonization of the relationship with the environment. Determination of the price would reduce the economic disparities in society, creating a more harmonious life, and enhance the dignity of mankind.